User satisfaction with health services and healthcare delivery in Cape Verde - da Luz Mendonça, Maria; de Fátima Carvalho Alves, Maria; Soares, Janice; Santos, Sónia; Silva, Maria Natalina; Lopes, Edna Duarte; Martins, Jailson Jesus; Ramos, Jessica; Ferreira, Pedro Lopes (BMC health services research, 2025)
The evaluation of health services and care is an important tool to define health policies. This study aimed at assessing user satisfaction with healthcare services, provided by public and private health facilities in Cape Verde. It was also our objective to analyze the sensitivity of satisfaction scores in relation to the respondent's sex. A cross-sectional, with a quantitative approach, was conducted. The study included individuals aged over 18 years. Participants were visiting a health facility at the time of the interview. All subjects signed an informed consent. Data were collected using a standardized self-administered questionnaire. Descriptive and inferential statistical analyses were performed using SPSS software, version 29. A total of 3,445 subjects took part in the study, 72% were women. The 25-45 age group accounted for 55.1% of the participants, 71.1% of whom declared themselves single. In general terms, women always gave higher satisfaction values. Specifically, in relation to age, those between 25 and 35 years old, single and with secondary education were more satisfied with professionals, access and social action and support, especially in private care. Those who were 45 years old or older better evaluate the care process. Previous consultation experience had a positive effect on women's satisfaction with professionals, facilities, access, social action and support and care process. On the contrary, the same areas of analysis, in hospitalization, were better evaluated by women without any previous experience. On the other hand, married or living together men were more satisfied with facilities and administrative services, and these services, as well as access, were better evaluated by those with less education. Men were also the most satisfied with the accessibility and costs on health centers, as well as hospital facilities. With regard to facilities and accessibility, the highest levels of satisfaction were found on the islands of Fogo and São Vicente. The highest level of dissatisfaction was found on the island of São Nicolau (facilities, access and social action and support), followed by the island of Sal (professionals and care process) and the island of Fogo (accessibility and administrative services). Our study suggests that the quality of healthcare services can be significantly improved, especially regarding access and accessibility to healthcare, drug policy and recruitment of qualified professionals.